Chinese Home-Based Cardiac Rehabilitation Model Delivered by Smartphone Interaction Improves Clinical Outcomes in Patients With Coronary Heart Disease - Ma, Jing; Ge, Cheng; Shi, Yajun; Xu, Yong; Zhao, Chenghui; Gao, Ling; Wen, Dongling; Li, Tengjing; Wang, Jinli; Yan, Sherry; Smith, Sidney C.; Chen, Yundai (Frontiers in Cardiovascular Medicine, 2021)
Purpose: We evaluated the long-term effect of a smartphone facilitated HBCR model in revascularized patients with coronary heart disease (CHD) on major adverse cardiac events (MACE), and secondary outcomes, including safety, quality of life, and physical capacity. Methods: A total of 335 CHD patients after successful percutaneous coronary intervention (PCI) was referred to the CR clinic in China between 7/23/2015 and 3/1/2018. Patients were assigned to two groups: HBCR tailored by monitoring and telecommunication via smartphone app (WeChat) (n=170) or usual care (control, n=165), with follow-up for up to 42 months. HBCR group received educational materials weekly and individualized exercise prescription monthly, and the control group only received 20-minute education at baseline in CR clinic. The primary outcome was MACE, analyzed by Cox regression models. The changes in the secondary outcomes were analyzed by the generalized linear regression model. Results: The median follow-up time was 29.6 months for both groups. Compared to the control group, HBCR group had a much lower incidence MACE (2.4% vs 8.5%, p=0.015), with adjusted HR= 0.27, 95% CI (0.09-0.82), also had reduced the unscheduled readmission (21.8% vs 10.0%, p=0.004), improved exercise capacity (maximal METs (5.6 vs. 6.1, p=0.001)), decreased anxiety scores, higher Seattle Angina Questionnaire score, and better control of risk factors. Subgroup analysis indicated that patients with a history of diabetes mellitus, smoking, or receiving statin therapy had the greatest benefit from HBCR. Conclusions: The Chinese HBCR model implemented using smartphone interaction is a safe and effective approach to decrease cardiovascular risks of patients with CHD and improve patient’s wellness.